Design and Evaluation of Hydrogel-Thickened Microemulsion for Topical Delivery of Minoxidil: Minoxidil Microemulsions for Topical Delivery - Sampathi Sunitha,; Wankar Jitendra,; Dodoala Sujatha,; Mankala Santhosh Kumar, (Iranian Journal of Pharmaceutical Sciences, 2013)
The available minoxidil formulations for topical application suffer with major drawback having less contact time with the scalp which requires repeated application. Hence, the present study was aimed to investigate the effect of microemulsions and microemulsion based hydrogel systems (MEHs) for increased percutaneous penetration of minoxidil. Minoxidil microemulsions were developed by following conventional titration method using oleic acid as oil phase, Tween 80 as surfactant and polyethyleneglycol 200 as co-surfactant. Smix is a surfactant and co-surfactant mixture, whose ratios in the mixture were optimized using the pseudo ternary phase diagram. The physicochemical interaction between the drug and polymer were investigated by FTIR. Prepared microemulsions and MEHs were evaluated for drug content, viscosity, pH, in vitro, ex vivo permeation, skin irritation and stability studies. The drug content and viscosity in prepared microemulsions was found ranged from 56.77±2.88 to 92.85±1.59 %, and 89.12±1.801 to 144.24±0.95 cps respectively. The Ex vitro skin permeation from these microemulsions was sustained over 24 h with drug release around 32±3.26 to 99±3.78 % with more retardation in formulation F4 (oleic acid:Smix:water 58%:40%:2%). F4 was incorporated into hydroxypropyl cellulose gel to get MEH formulation and both were compared with the marketed topical solution. Marketed preparation was diffused at faster rate in comparison to the microemulsion and MEH. The drug release order was found to be Higuchi’s with non-Fickian “anomalous” mechanism at controlled rate. The flux of the microemulsion F4 and MEH was found around 70.11±10.81 and 90.26±11.46 (μg/cm2/hr) with permeation coefficient around 27.18±6.69 and 30.21±5.16 (cm/hr). The microemulsion did not show any dermatological reactions when tested. The microemulsion was found stable on storage and results suggested that microemulsions and MEHs could be more promising for topical delivery of minoxidil in hair loss treatment in comparison to solution based formulations.